The Influence of Job Satisfaction and Work Motivation towards Organizational Citizenship Behavior (OCB) (Study At Bank Jatim Malang Branch) - Kamilia, Ghina Indah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims to determine the effect of job satisfaction and simultaneous and partial work motivation on the organizational citizenship behavior (OCB) employees of Bank Jatim Malang Branch. Type of research used is causal research. The population used is four parts of Bank Jatim Malang Branch, which is the marketing of teller, credit, and customer service with a sample of 78 employees. Sampling using purposive sampling technique with work features on the teller, customer service, marketing, and credit. Analyzer used is multiple linear regression. To test the hypothesis used F test and t test. Results from multiple regression analysis show. Job satisfaction and work motivation simultaneously on Organization Citizenship Behavior (OCB) employees. In addition, available results for non-significant job satisfaction variables on 'Organizational Citizenship Behavior (OCB) and significant work motivation for employees' Organizational Citizenship Behavior (OCB). Then seen from the value of Adjusted R Square shows the influence between the variables 0.380 which means the influence between job satisfaction and work motivation to Organizational Citizenship Behavior (OCB) employees of 38.0% while the remaining 62.0% explained by other variables not examined in this research.KEYWORDS: Job Satisfaction, work motivation, Organizational Citizenship Behavior (OCB).